Childhood idiopathic pulmonary arterial hypertension: a national cohort study. Issue 17 (20th April 2010) - Moledina, S; Hislop, A A; Foster, H; Schulze-Neick, I; Haworth, S G
Abstract : Objective: To clarify the clinical characteristics and epidemiology of idiopathic pulmonary arterial hypertension (IPAH) in childhood, a rare condition with a bad prognosis, poorly documented in children. Also, to describe the long-term outcome. Design: A retrospective study of 7 years' experience. Setting: UK Service for Pulmonary Hypertension in Children based at a tertiary referral centre. Patients: 64 children. Interventions: Patients were initially treated with prostanoids (n=15), bosentan (n=23), sildenafil (n=9), combination therapy (n=11) or calcium channel antagonists (n=6). Main outcome measures: WHO functional class, distance walked in 6 minutes, escalation of therapy, survival, transplant-free survival. Results: Incidence of IPAH was 0.48 cases per million children per year and the prevalence was 2.1 cases per million. 31% presented with syncope. Oedema was rare. During the first year of follow-up WHO functional class and 6-minute walk distance improved significantly. Survival at 1, 3 and 5 years was 89%, 84% and 75%, respectively; while transplant-free survival was 89% 76% and 57%, respectively. Factors predicting worse survival were WHO functional class (HR 2.4, p=0.04) and poor height and weight z-score (p<0.05 for both) at presentation. Conclusions: We showed, for the first time, that the incidence of IPAH is lower in children than adults and that the clinical features can be different. Most children present with clinical evidence of advanced disease and clinical status at presentation is predictive of outcome. This 7-year experience confirms the significant improvement in survival over historical controls.